Synthesis, Characterization, Antibacterial and Wound Healing Efficacy of Silver Nanoparticles From Azadirachta indica - Chinnasamy, Gandhimathi; Chandrasekharan, Smitha; Koh, Tong Wey; Bhatnagar, Somika (Frontiers in Microbiology, 2021)
Bacteria are the causative agents of numerous diseases. Ever increasing numbers of bacterial infections have generated the need to find new antibiotic materials and new ways to combat bacterial infections. Our study investigated Azadirachta indica (AI) as an alternate source of antibiotic compounds. Phytochemical and GC-MS analysis revealed presence of flavonoids, phenolic compounds, terpenoids and terpenes. Aqueous extracts of leaves were used to synthesize silver nanoparticles (AI-AgNPs), as established by colorimetric confirmation with maximum absorbance peak at 400 nm. Optimized reaction parameters produced high yield of stable AI-AgNPs, which were characterized by UV-Vis, EDX, SEM, and TEM. Results confirmed 33 nm, spherical AI-AgNPs. FTIR inferred the presence of functional groups in bioactive constituents involved in conversion of silver ions into elemental silver by acting as capping and reducing agents during formation of AI-AgNPs. XRD revealed their crystalline nature. Toxicity studies on Drosophila validated normal egg laying capacity and eclosion of F1 generation on AI-AgNPs (100 µg/mL). DPPH (65.17%) and ABTS (66.20%) assays affirmed strong radical scavenging effect of AI-AgNPs (500 µg/mL). The antibacterial activity of AI-AgNPs (1000 µg/mL) was confirmed by disc diffusion assay with zone of inhibition (ZOI) against Bacillus cereus (17.7 mm), Escherichia coli (18.7 mm), Pseudomonas aeruginosa (10.3 mm), and Staphylococcus aureus (17.7 mm). MIC and MBC values for AI-AgNPs ranged between 390-780 µg/mL. Higher bacterial suppression by AI-AgNPs in comparison with AI-extract was further divulged by prominent damage to the bacterial cell walls, disintegration of cell membranes and outflow of intercellular content as evident in SEM images. AI-AgNPs were loaded on PF127 (biocompatible-biodegradable polymer) to form a viscous, spreadable, hydrogel that demonstrated enhanced antibacterial properties in disc diffusion assay (13-18.7 mm). When topically applied on mice, AI-AgNPs-PF127 hydrogel did not show symptoms of skin irritation. Application of AI-AgNPs-PF127 hydrogel on wound sites in mice, significantly increased the wound contraction rate. Our studies present a simple green route to synthesize AI-AgNPs with enhanced antibacterial and free-radical scavenging efficacy; and AI-AgNPs-PF127 hydrogel as a low-toxic, eco-friendly delivery vehicle with potential in wound healing.